(untitled) (Journal of Economic Research & Business Administration, 2015)
The source of different troubles in the economy to see some models of government, the second - in the unit, and the third - in the next change science-technological production order. Analyzing the complex nature of the 2008 global crisis, many experts are inclined to believe that the source of all the troubles and turmoil is inflation, it even considered the scourge of the sustainable development of the market economy. Is it itself th fact? In this report, the author presents his vision of the answer to this important question, and, in their view, it is clearly negative. In particular, the document provides specific and substantiated cases where high inflation is the driving force, not the scourge of the market economy